Construction Business Process Reengineering (CBPR): A Case Study of Construction Organizations in Malaysia - Sabki, O.W.M.; Nawi, M.N. Mohd; Mohamed, O.; Azzli, F. (Jurnal Teknik Sipil, 2005)
Abstract. Business Process Reengineering (BPR) is currently one of the most popular catchwords. Companies hope to break the "magic triangle" of costs, time and quality by streamlining theirÂ  business processes. So far, most BPR projects have concentrated on stationary industries, mainly manufacturing. Others, such as the construction industry, have not gained as much attention yet, even though there is a high need for reducing costs and improving the effectiveness in this industry. Increasing customer demands towards quality, speed and flexibility, tough competition from international companies, and reduced public spending have created a difficult situation for many construction organizations in Malaysia. In order to adopt BPR within construction industry and prevent from lagging behind other sectors, this study theoretically assessed effectiveness and deficiencies of the âtraditionalâ organizations as well as the factors that cause those effects in comparison with the âeffectiveâ organizations based on the BPR concepts. By contrasting what are found in âeffectiveâ organizations but not found inâ traditionalâ organizations, critical attributes that contribute the most to successful adoption of BPR were identified so that the improvement steps for applying BPR can be suitable focused. The validated findings indicated remarkable contrast between âtraditionalâ and âeffectiveâ organizations. Five critical aspects including establishment performance measurement system, empowerment of employees, participation of top management, innovative organization, and information technology (IT) were found to be the major differences to be applying BPR.